2009
DOI: 10.2217/fon.09.10
|View full text |Cite
|
Sign up to set email alerts
|

EGF-Receptor Regulation of Matrix Metalloproteinases in Epithelial Ovarian Carcinoma

Abstract: Ovarian carcinoma is most frequently detected when disease has already disseminated intraabdominally, resulting in a 5-year survival rate of less than 20% owing to complications of metastasis. Peritoneal ascites is often present, establishing a unique microenvironmental niche comprised of tumor and inflammatory cells, along with a wide range of bioactive soluble factors, several of which stimulate the EGF-receptor (EGFR). Elevated EGFR is associated with less favorable disease outcome in ovarian cancer, relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 140 publications
(220 reference statements)
0
36
0
Order By: Relevance
“…This work may have clinical significance given that the ovarian tumor environment contains numerous EGFR activators 2 and approximately 35% of all ovarian cancer tumors are positive for activated EGFR. 3,4 Using an in vitro paradigm of EGF exposure of OVCA 433 cells, we found that acute and long-term EGFR activation increases DNMT activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This work may have clinical significance given that the ovarian tumor environment contains numerous EGFR activators 2 and approximately 35% of all ovarian cancer tumors are positive for activated EGFR. 3,4 Using an in vitro paradigm of EGF exposure of OVCA 433 cells, we found that acute and long-term EGFR activation increases DNMT activity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Ovarian cancer progression is characterized by the accumulation of ascites in which there are several activators of epidermal growth factor receptor (EGFR) including heparin-binding EGF (HB-EGF), endothelin-1 (ET-1) and lysophosphatidic acid (LPA). 2 The presence of these activators in patient ascites suggests that the tumor microenvironment is under chronic EGFR activation and may account for the observation that approximately 35% of all ovarian cancer tumors are positive for activated EGFR (tyrosine phosphorylated EGFR). 3,4 Overexpression of EGFR, and its ligands, has been detected in ovarian tumors and correlates with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter leads to the stimulation of numerous downstream signaling cascades associated with cell growth and survival, angiogenesis, and tumor metastasis. In EOC, EGFR expression has been reported to be in the range of 10%-70% (with an average of 50%) [44] and EGFR amplification has been reported to be in the range of 1%-6% of cases [45]. Indeed, studies on prostate cancer cells suggest that there is crosstalk between AR and EGFR [46].…”
Section: Ar Signaling In Eocmentioning
confidence: 99%